Student Engagement and Factors Affecting Active Learning in English Language Teaching - Daniel Ginting (VELES Voices of English Language Education Society, 2021)
Learning is the process of how students take information and relate it to their prior knowledge into something meaningful. Learning promotes continuous growth and change in students. Student engagement is considered one of the significant predictors of successful learning. In general, student engagement refers to the active participation in a series of academic and co-curricular or school-related activities and commitment to pursuing learning goals. Does student engagement associated with successful learning occur in any settings, offline or online programs? This paper presents some theoretical frameworks about student engagement. This paper concludes with some pedagogical implications for English language teaching techniques.